A Rare Metastasis to the Bladder. (3rd March 2013) - Modh, Rishi A.; Corbyons, Katherine A.; Yeung, Lawrence L.
Abstract : Primary bladder cancer is the fifth most common malignancy but secondary malignancies of the bladder are rare. Distinguishing primary adenocarcinomas of the bladder from secondary adenocarcinomas is difficult and relies on immunohistochemical staining. Prostate, colorectal, breast, and lung all can produce metastatic adenocarcinomas to the bladder. Further management of the malignancy varies depending on the source, thus making proper diagnosis critical. We present only the fifth documented case of metastatic adenocarcinoma of the lung to bladder and performed a review of the literature.